The tenure of the local executive tenures on the example of local government elections in the Łódź voivodeship - Ewelina Stasiak (Acta Universitatis Lodziensis: Folia Sociologica, 2024)
The article concerns issues related to the tenure of the executive body in Polish local government units. The paper aims to make a spatial analysis of the phenomenon of multicadency of mayors in Łódź voivodeship. The study was carried out in two dimensions: spatial (rural municipalities in Łódź voivodeship) and temporal (local government elections in 2002, 2006, 2010, 2014 and 2018). The analysis based on data from the State Election Commission revealed that re-election is a frequent phenomenon in the rural municipalities of Łódź voivodeship. It is probably because local authorities respond to the needs and expectations of voters. This strengthens their positive feelings, increases satisfaction and leads to the formation of positive motives for participation in local government elections and election decisions (identified with the re-election of the municipal executive).